Methodological Recommendations for the Formation of Managerial Competence of Future Officers of Communication Units in the Process of Professional Training - Pavlenko, Oleh (Pedagogical Discourse, 2024)
problem of formation of managerial competence of future officers of the Armed Forces of Ukraine’s communication units in the process of professional training. The author insists that the main methodological recommendations are as follows: awareness of the process of forming the managerial competence of officers of communication units as an integral part of the system of professional training of future officers; selection of content and design of professional training for future officers of communication units, taking into account current needs and preparation for managing units in combat conditions; introducing NATO management standards into the educational process of higher education institutions based on an adaptive approach and improving the professional competence of academic staff to apply them; development of professional communicative competence of future officers, including foreign language competence, for effective management activities, as well as organization of independent cognitive activity of cadets through the development of their leadership skills and self-management; integration of managerial knowledge, skills and abilities on the basis of an interdisciplinary approach into the educational process of higher education institutions; ensuring an innovative pedagogical environment in higher education institutions; introducing the best foreign experience in the formation of managerial competence of future officers; ensuring teaching based on the combat experience of the academic staff of higher education institutions who participated in combat operations to protect Ukrain from the russian aggressor. Also, it is important to improve the content, forms and methods of professional training of cadets of higher military education institutions, ensuring unity, organic interconnection of professional, managerial and leadership training of future officers of communication units based on the principles of flexible design, predictability, and the graduated nature of higher education and introducing the principles of student-centered and competency-based approach into the methodology of teaching general military and professionally oriented disciplines.